Photonic simulation method applied to the study of structural color in Myxomycetes - Dolinko, Andrés Ezequiel (2012)
We present a novel simulation method to investigate the multicolored effect of the Diachea leucopoda (Physarales order, Myxomycetes class), which is a microorganism that has a characteristic pointillistic iridescent appearance. It was shown that this appearance is of structural origin, and is produced within the peridium -protective layer that encloses the mass of spores-, which is basically a corrugated sheet of a transparent material. The main characteristics of the observed color were explained in terms of interference effects using a simple model of homogeneous planar slab. In this paper we apply a novel simulation method to investigate the electromagnetic response of such structure in more detail, i.e., taking into account the inhomogeneities of the biological material within the peridium and its curvature. We show that both features, which could not be considered within the simplified model, affect the observed color. The proposed method is of great potential for the study of biological structures, which present a high degree of complexity in the geometrical shapes as well as in the materials involved. © 2012 Optical Society of America.